Anatomically informed deep learning framework for generating fast, low-dose synthetic CBCT for prostate radiotherapy - Kadhim, Mustafa; Persson, Emilia; Haraldsson, André; Gustafsson, Christian Jamtheim; Nilsson, Mikael ; 0000-0003-1712-8345; Kügele, Malin ; 0000-0002-7213-111X; Bäck, Sven; Ceberg, Sofie (Scientific Reports, 2025)
Precise patient positioning and daily anatomical verification are crucial in external beam radiotherapy to ensure accurate dose delivery and minimize harm to healthy tissues. However, Current image-guided radiotherapy techniques struggle to balance high-quality volumetric anatomical visualization and rapid low-dose imaging. Addressing this, reconstructing volumetric images from ultra-sparse X-ray projections holds promise for significantly reducing patient radiation exposure and potentially enabling real-time anatomy verification. Here, we present a novel DL-based framework that generates synthetic volumetric cone-beam CT in real-time from two orthogonal projection views and a reference planning CT for prostate cancer patients. Our model learns the mapping between 2D and 3D domains and generalizes across patients without retraining. We demonstrate that our framework produces high-fidelity volumetric reconstructions in real-time, potentially supporting clinical workflows without hardware modifications. This approach could reduce imaging dose and treatment time while preserving comprehensive anatomical information, offering a pathway for safer, more efficient prostate radiotherapy workflows.